(untitled) - Tubbs, Stewart L. (New York, 1991)
This revision of a text for introductory survey courses in speech communication stresses theory, research, and applications. The book is divided into two parts and covers The general pinciples of communication, listening, perception and non verbal communication. More specifically, the authors examine interpersonal communication, interviewing, group discussion, public speaking, organizational communication, mass media, intercultural communication, thereby giving students an overview of all the major areas of communication
Keywords: Communication,Truyền thông